1986
DOI: 10.1111/j.1365-2141.1986.tb05544.x
|View full text |Cite
|
Sign up to set email alerts
|

Graft rejection following HLA matched T‐lymphocyte depleted bone marrow transplantation

Abstract: Summary. Bone marrow graft rejection following HLA‐matched bone marrow transplantation (BMT) for leukaemia has been a rare problem. However, with the introduction of T‐lymphocyte depleted BMT, graft rejection is recognized as a new complication. At the Royal Free Hospital (RFH) in London T‐depletion is achieved using two monoclonal antibodies with complement mediated lysis. The methodology was extended to other centres and in total 56 patients have received T‐depleted, HLA matched BMT. Twelve of 56 patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…It can be prevented by selected methods, but often at the expense of an increased risk of relapse, rejection or delayed immune reconstitution. [1][2][3] Hence, no optimal or even satisfactory prevention and treatment method can be defined. To advance our knowledge and define optimal approaches, correct information on the value of different strategies and methods in GVHD prevention and treatment is essential.…”
Section: Introductionmentioning
confidence: 99%
“…It can be prevented by selected methods, but often at the expense of an increased risk of relapse, rejection or delayed immune reconstitution. [1][2][3] Hence, no optimal or even satisfactory prevention and treatment method can be defined. To advance our knowledge and define optimal approaches, correct information on the value of different strategies and methods in GVHD prevention and treatment is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Negative selection can be achieved either through physical methods such as counterflow elutriation [3,4,5] or soybean lectin agglutination (SBA) and sheep red blood cell (sRBC)-rosette depletion (E-rosetting) [6,7,8,9,10], or immunological methods using monoclonal antibodies [5,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. Monoclonal antibodies can be used with or without complement, or conjugated to toxins.…”
Section: T-cell Depletion Techniquesmentioning
confidence: 99%
“…Multiple animal and clinical studies have shown the dichotomous role of T cells in donor engraftment and GVHD [4,5,[11][12][13][14][15] . With recently available canine CD3 and CD5 antibodies, we have advanced our model to begin to adjust the donor graft for T-cell dosaging.…”
Section: Commentmentioning
confidence: 99%